Significance of chaperonin 10-mediated inhibition of ATP hydrolysis by chaperonin 60 - Dubaquié, Yves (The National Academy of Sciences of the USA, 1997)
Chaperonins are essential for the folding of proteins in bacteria, mitochondria, and chloroplasts. We have functionally characterized the yeast mitochondrial chaperonins hsp60 and hsp10. In the presence of ADP, one molecule of hsp10 binds to hsp60 with an apparent K(d) of 0.9 nM and a second molecule of hsp10 binds with a K(d) of 24 nM. In the presence of ATP, the purified yeast chaperonins mediate the refolding of mitochondrial malate dehydrogenase. Hsp10 inhibits the ATPase activity of hsp60 by about 40%. Hsp10(P36H) is a point mutant of hsp10 that confers temperature-sensitive growth to yeast. Consistent with the in vivo phenotype, refolding of mitochondrial malate dehydrogenase in the presence of purified hsp10(P36H) and hsp60 is reduced at 25°C and abolished at 30°C. The affinity of hsp10(P36H) to hsp60 as well as to Escherichia coli GroEL is reduced. However, this decrease in affinity does not correlate with the functional defect, because hsp10(P36H) fully assists the GroEL-mediated refolding of malate dehydrogenase at 30°C. Refolding activity, rather, correlates with the ability of hsp10(P36H) to inhibit the ATPase of GroEL but not that of hsp60. Based on our findings, we propose that the inhibition of ATP hydrolysis is mechanistically coupled to chaperonin-mediated protein folding.